The baseline examinations of the German National Cohort (NAKO): recruitment protocol, response, and weighting - Rach, Stefan; Sand, Matthias; Reineke, Achim; Becher, Heiko; Greiser, Karin Halina; Wolf, Kathrin; Wirkner, Kerstin; Schmidt, Carsten Oliver; Schipf, Sabine; Jöckel, Karl-Heinz; Krist, Lilian; Ahrens, Wolfgang; et al. (European journal of epidemiology, 2025)
The German National Cohort (NAKO) is the largest population-based epidemiologic cohort study in Germany and investigates the causes of the most common chronic diseases. Between 2014 and 2019, a total of 1.3 million residents aged 20-69 years from 16 German regions were randomly selected from the general population and invited to participate following a highly standardized recruitment protocol. The overall response was 15.6% and differed considerably across study centers (7.6-30.7%). Females were more likely to participate than males (17.5% vs. 14.1%) and participation increased with age (10.2% in age group “ < 29 years” up to 20.7% in age group “ > 60 years”). Across all study regions, response was highest in rural areas (22.3%), followed by towns and suburbs (17.2%), and was lowest in cities (14.5%). Compared with the general population in the respective study regions, participants with low and medium education are underrepresented in the NAKO sample, while highly educated participants are overrepresented. Participants with non-German nationality and with a migration background are also underrepresented. Participants living in single households are underrepresented, while participants from larger households (2 or more persons) are overrepresented compared to the general population. Survey weights are made available to researchers along with the study data that account for the sampling design and adjust for differences in the distribution of age, sex, nationality (German vs. non-German), migration status, education, and household size.